Ultrasound treatment enhanced the functional properties of phycocyanin with phlorotannin from Ascophyllum nodosum - Bai, Ying; Li, Xueting; Xie, Yuqianqian; Wang, Yingzhen; Dong, Xiuping; Qi, Hang (Frontiers in Nutrition, 2023)
Phycocyanin (PC) and phlorotannin from Ascophyllum nodosum (A. nodosum) with various biological activities can combine to form complexes. In this work, the impact of ultrasound treatment on the complex of PC and phlorotannin structural and functional characteristics was carefully investigated. The interaction between PC and phlorotannin after ultrasound treatment was studied by UV-Vis and fluorescence and circular dichroism (CD) spectroscopy. This was manifested as the UV--Vis spectrum reduction effect, fluorescence quenching effect and weak conformational change of the CD spectrum of PC. The PC was identified as amorphous based on the X-ray diffraction (XRD) data and that phlorotannin was embedded into the PC matrix. The differential scanning calorimetry (DSC) results showed that ultrasound treatment and the addition of phlorotannin could improve the denaturation peak temperatures (Td) of PC to 78.7 ℃. In vitro digestion and free radical scavenging experiments showed that appropriate ultrasound treatment and the addition of phlorotannin were more resistant to simulated gastrointestinal conditions and could improve DPPH and ABTS+ free radical scavenging performance. Therefore, ultrasound treatment and the addition of phlorotannin changed the structural and functional properties of PC. These results demonstrated the feasibility of ultrasound-assisted phlorotannin from A. nodosum in improving the functional properties of PC and provided a possibility for the application of PC-polyphenol complexes in the food industry.